2009
DOI: 10.1002/cncr.24776
|View full text |Cite
|
Sign up to set email alerts
|

Complex care systems in developing countries

Abstract: BACKGROUND:As the global visibility and importance of breast cancer increases, especially in developing countries, ensuring that countries strengthen and develop health systems that support prevention, diagnosis, and treatment of a complex chronic disease is a priority. Understanding how breast cancer patients navigate health systems to reach appropriate levels of care is critical in assessing and improving the health system response in countries to an increasing breast cancer burden in their populations. Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 22 publications
2
50
2
Order By: Relevance
“…Unlike a recent study in Ethiopia examining breast cancer patient navigation through the health care system which found that patients typically visited three health facilities before being referred to a specialized cancer center, 21 most patients in our study had arrived at the TCC by the third node of care. However, on average, patients in our study experienced longer system delays than patients in studies conducted on other international populations in both developed and developing countries.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Unlike a recent study in Ethiopia examining breast cancer patient navigation through the health care system which found that patients typically visited three health facilities before being referred to a specialized cancer center, 21 most patients in our study had arrived at the TCC by the third node of care. However, on average, patients in our study experienced longer system delays than patients in studies conducted on other international populations in both developed and developing countries.…”
Section: Discussioncontrasting
confidence: 64%
“…Finally, patients who initially visited a general surgeon followed by a visit to a surgical oncologist were more likely face a delay in reaching the TCC as a result of the Egyptian health care system. Thus, the type of physician a patient comes in contact with initially as well as the patient’s navigation pathway play an important role in obtaining timely treatment, 10,21 indicating that barriers to breast cancer diagnosis and treatment exist within the Egyptian health care system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Through the analysis of sources of delay in accessing medical care in low-income nations, the following themes have emerged as the fundamental causes: Cultural beliefs and practices, financial restrictions, knowledge and skills of primary care providers and the public's perception of same, and transportation. [8911222931]…”
Section: Introductionmentioning
confidence: 99%
“…The patient navigation chain has a lot of barriers until the patients eventually reach the central cancer center. At a minimum, patients face 3 or more nodes that are widely divergent [44]. A study done in Ghana found that being a member of the Islamic religion, seeking treatment at traditional healers, and a lack of awareness of national health insurance coverage for BC treatment were the main factors that affected treatment completion [45].…”
Section: Cancer Control In Africamentioning
confidence: 99%